PERFORMANCE OF SOCIAL AGENCY ON HANDLING THE HOMELESS in MANADO CITY - RIMBING, GRACELLA; LENGKONG, FLORENCE DAICY; POMBENGI, JERICHO (JURNAL ADMINISTRASI PUBLIK, 2018)
Abstract: This research is a qualitative research to examine the performance of Manado City Social and Community Empowerment Agency in handling the homeless in Manado City, using performance indicator according to Dwiyanto: Productivity, Service Quality, Responsiveness, Responsibility, and Accountability. Data were obtained through interviews, completed with secondary data, in the form of data from the Manado Social Service and Manado city newspapers. The number of informants in this study is 7 people, consisting of: 2 employees of Manado City Social Service, 3 homeless people located in Manado city, and 2 people who often see the daily life of the homeless. From the results of the research, obtained; (1) In terms of productivity, the performance of Manado City Social and Community Empowerment Agency in handling the homeless is still minimal. (2) In terms of service quality, the performance of Manado City Social and Community Empowerment Agency in handling the homeless is still minimal. (3) In terms of responsiveness, the performance of Manado City Social and Community Empowerment Agency in handling the homeless in Manado is still minimal. (4) In terms of responsibilitas, Manado City Social and Community Empowerment Agency in handling the homeless is quite enough. (5) In terms of accountability, the performance of Manado City Social and Community Empowerment Agency in handling the homeless is quite enough. Keyword: Performance, Social Agency, Homeless